KERUKUNAN ANTARAGAMA PERSPEKTIF FILSAFAT PERENNIAL: REKONSTRUKSI PEMIKIRAN FRITHJOF SCHUON - Ngainun Naim (Harmoni, 2012)
Religion is an integral part of human life. In fact, there are many problems must be solved. Religion still faces various heavy challenges. One of them is problem on interaction among the different religious followers. In this case religion is often used as practical interest that opposite to the religion’s dogma, like conflicts and violence among the followers. The phenomena concerns many religious leaders. The philosopher, Frithjof Schuan judged that those cases happened in relation with many deviations in religious doctrines that imply religious value and right. Actually religion teaches peace, tolerance and rewards to others. Problems interreligious followers problems in Indonesia are never solved, there are many conflicts happened from time to time. This study gives kind of solutions in order to create harmony among different religious followers in Indonesia.